TV Publik dan Lokalitas Budaya: Urgensinya di Tengah Dominasi TV Swasta Jakarta - Puji Rianto; Intania Poerwaningtias (Program Studi Ilmu Komunikasi, 2013)
This article discusses about public service broadcasting and the urgency of culture program, especially the local culture program. This discussion based on the argument that broadcasting in Indonesia is dominated by private television that considered rating as the principal goal. In the other hand, local culture programs are ignored as the result of centralized broadcasting system. In fact, local culture program is very required. It is showed by the popularity of culture program “Pangkur Jenggleng” that shows on TVRI Jogja. For public service broadcasting, culture program is one of their duty and mission that must be carried on.